Comparative Evaluation Of The Effectiveness Of Dexamethasone And Adrenaline With 2% Lignocaine For Pterygomandibular Nerve Blocks: A Randomized Controlled Clinical Study (Bangladesh Journal of Medical Science, 2023)
Background and Aim: Dexamethasone, a glucocorticoid, has been used in local anesthetics as an additive for various locoregional nerve blocks. Although, its use in the dental field has not been unexplored and concealed. The current study was conducted to evaluate and compare the calibre of anesthesia, their hemodynamic response, vasoconstrictive effects, and control of pain while administering pterygomandibular nerve blocks using 2% Lignocaine hydrochloride solution with Dexamethasone(4mg/ml) with that of the standard 2% Lignocaine hydrochloride solution and Adrenaline bitartrate (1:80000).Materials and Methods: This triple-blind randomized controlled study included 80 healthy subjects, aged between 18-45 years with an indication for surgical removal of impacted mandibular third molars. With the aid of a computer-generated sequence, the subjects were arbitrarily assigned into 2 groups (40/group)- Group 1: patients administered with 2% Lignocaine hydrochloride and Dexamethasone Sodium Phosphate (4mg/ml) solution, and Group 2: patients administered with 2% Lignocaine hydrochloride with Adrenaline bitartrate (Adr) 1: 80,000 (12.5 μgm/ml) solution. The variables were assessed based on their time of onset, depth (pain) and duration of anesthesia, systolic, diastolic, and mean arterial blood pressures, heart rate, and blood loss.Results: Statistically significant difference (P0.05) for pain, blood loss, cardiovascular variables (systolic, diastolic and mean arterial blood pressures and heart rate) at various intervals was noted.Conclusion: Dexamethasone added to Lignocaine shortens onset, prolongs duration of action and yields better control of post-operative pain as compared to Lignocaine with Adr. Vasoconstrictive properties, hemodynamic variables and intra-op pain control were comparable.Bangladesh Journal of Medical Science Vol.22 (Special Issue) 2023 p.172-178